Nanomaterial Antibacterial Technology in the Design of Antibacterial Fabrics for Sports Clothing. (27th October 2021) - Feng, Yuan
Abstract : In recent years, nanomaterials have been widely used in sports equipment, and their application in sportswear has also attracted wide attention. This research mainly discusses the application of nanomaterial antibacterial technology in the design of antibacterial fabrics for sports apparel. The method of adding nano-TiO2 to the antibacterial textiles varies with the type of fiber or fabric, and the finishing method also changes accordingly. For chemical fibers, the method of blending spinning is mainly used. By adding nano-antibacterial particles in the spinning solution, the polymer is ejected from the spinneret to make antibacterial fibers. This processing method is characterized by good antibacterial durability. The preparation of antimite finishing agent is mainly the dispersion of nanopowder. The selection of the best dispersant is mainly determined by measuring the change of the volume sedimentation rate of TiO2 after 5 days under different dosage and pH value of each dispersant. Then, the particle size of nano-TiO2 and Ag in different dispersing conditions was tested by TEM, and finally, the best dispersing agent and dispersing process were determined. The optimum of nano-antimite and antibacterial finishing agent is as follows: the dispersing agent is TW-80, the amount of anhydrous ethanol in dispersing medium is 5 times that of powder, the amount of dispersing agent is 1.5 times that of powder, the pH value is 7, and the stirring time is not less than 30 min. In the preparation of nano-antimite and antibacterial finishing agent, nanomaterials were used. The weight of nano-TiO2 powder was 20 grams and that of Ag was 20 grams. The dispersion medium (absolute ethanol) was 100 mL of dispersant. The amount of TW-80 was 30 g, the amount of citric acid was 60 g, the emulsion was very stable, and there was only a small amount of precipitation after being static for 5 days. Considering the characteristics of silk knitted fabric, this experiment uses the exhaustion method in the finishing process to finish the silk knitted fabric. After 50 times of washing, the antibacterial rate of Staphylococcus aureus and Escherichia coli reached 95.13% and 87.44%, respectively. This study provides guidance for the application of nanomaterials in the antibacterial field of sports clothing.